Reducing VNS stimulation parameters: Is it safe? - Oliveira, Tatiana Von Hertwig Fernandes de; Chaves, Jennyfer Paulla Galdino; Silva, Thiago Teixeira; Francisco, Alexandre Novicki; Stebel, Sérgio Leandro (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Introduction Vagal nerve stimulation (VNS) is an adjuvant therapy used in the treatment of patients with refractory epilepsy who are not candidates for resective surgery or who have limited results after surgical procedures. Currently, there is enough evidence to support its use in patients with various types of epilepsy. Therefore, the present study was conducted to explore the possibility of optimizing therapy by reducing the consumption of the system's battery.Methods The prospective and double-blind analysis consisted in the evaluation of 6 patients submitted to VNS implantation for 3 months, followed by adjustment of the stimulation settings and continuity of follow-up for another month. The standard protocol was replaced by another with a frequency value of 20 Hz instead of 30 Hz to increase battery life. The safety of this procedure was evaluated through the assessment of two main variables: seizures and side effects.Results The stimulation at 20 Hz showed 68% reduction in the incidence of seizures (p = 0.054) as well as low incidence of side effects.Conclusion The present study suggests that the reduction of the stimulation frequency from 30 to 20 Hz is a safe procedure, and it does not compromise the effectiveness of therapy.
Keywords: vagus nerve stimulation; vagal stimulation; VNS; refractory epilepsy